Eficiência de reflorestamentos nativos e exóticos na recuperação de interações formiga-planta em uma paisagem agroflorestal na Amazônia Meridional - Falcão, Jéssica Caroline de Faria (2012)
Recently, various reforestation programs have been created in the Brazilian Amazon in order to restoring the biological diversity in deforested environments. However, most studies have focused only on species loss and ignored the loss of ecological interactions and ecosystem services involving these species in their natural environment. In this study, we used metrics derived from ecological networks to evaluate the role of reforestation, natural regenerationand the distance of the forest matrix, on the mutualistic interactions between ants and plants with extrafloral nectaries (EFN) in a rainforest within the southern Brazilian Amazon. We showed that the distance of the forest did not influence the restoration of ant-plant networks. Moreover, we also showed that reforestations of the exotic and native species (Tectona grandis and Ficus maxima) and environments of natural regeneration had the same efficiency in recovering the diversity of antplant interactions in relation to pasture. We also found no difference in the specificity of ant-plant interactions between the reforestation of T. grandis, environments of natural regeneration and the forest. Reforestation of F. Maxima had the same specificity of interactions that pasture. Additionally, the nestedness value of networks also did not vary among the environments studied, which indicate that the topological structure of ant-plant networks can be stable independently of local environmental factors. In short, we showed that the natural regeneration may be the more efficient and economical method to restoring the diversity and structure of ant-plants with EFN interactions in tropical forests.